El empoderamiento ciudadano y su influencia en la gestión pública del Gobierno Regional de La Libertad - Cueva Zavaleta, Jorge Luis (2019)
ABSTRACT The thesis entitled: Citizen empowerment and its influence on the public management of the Regional Government of La Libertad, had as a central objective to determine how the empowerment of Citizen Participation would influence with voice and vote for the control and oversight of public management, in the effectiveness and efficiency in achieving the social objectives of the Regional Government of La Libertad. The study sample was constituted by the budget execution assigned to the Regional Government of La Libertad in the period 2011-2018 and its consolidated; as well as by 10 public officials of the Regional Government of La Libertad to obtain information on public management in said region; and for 40 citizens of the La Libertad Region, to gather information about their participation in the public management of the Regional Government of La Libertad; besides the legislation that regulates citizen participation. Likewise, the study of the Constitution, the Decentralization Law and the State Contracting Law were considered, in order to determine their scope and on how they regulate regional public management. In order to gather information on the effectiveness, efficiency and citizen participation in the public management of the Regional Government of La Libertad, the techniques of documentary analysis were used to obtain data on budget executions from the Regional Government of La Libertad in the 2011 period. -2018, and the technique of the survey to obtain information from 10 public officials on public management in the period under study, and 40 citizens of the La Libertad Region, for which the document analysis guide tools and the survey questionnaire were used. The information was processed and presented in tables with the design of the statistical processor SPSS 10.0. The most important results were: that in the 2011-2018 period only an average of 49.23% of the allocated budget was spent, so the public management of the Regional Government of La Libertad was inefficient and inefficient in the execution of its budget and that There is a disinterest in the population to intervene in public affairs, the main cause being: that citizen participation is only a formality that is not taken into account when making public decisions. It was concluded that the empowerment of Citizen Participation with voice and vote for the supervision of Public Management, would influence in a greater effectiveness and efficiency in the achievement of the social objectives of the Regional Government of La Libertad.